THE CHOICE BETWEEN MERGERS/ACQUISITIONS AND JOINT VENTURES: THE CASE OF JAPANESE INVESTORS IN THE UNITED STATES - Hennart, Jean‐François; Reddy, Sabine (Strategic Management Journal, 1997)
This paper investigates the determinants of the choice between two alternative methods of pooling similar and complementary assets: the merger/acquisition and the greenfield equity joint venture. Two theories of the determinants of that choice are tested on a sample of Japanese investments in the United States. The results show that equity joint ventures are preferred over acquisitions when the desired assets are linked to nondesired assets because the U.S. firm owning them is large and not divisionalized, when the Japanese investor has little previous experience of the American market and hence seeks to avoid postmerger integration problems, when the Japanese investor and the U.S. partner manufacture the same product, and when the industry entered is growing neither very rapidly nor very slowly. © 1997 by John Wiley & Sons, Ltd.